If I asked the obvious because of my lack of knowledge, then I am sorry!

If $abcd=1,a,b,c,d>0$;prove:$$\sum_\limits{cyc}\frac{a}{a^2+a+1}\leq\sum_\limits{cyc}\frac{1}{a^2+a+1}$$

I use $f(x)=\frac{x-1}{x^2+x+1}$,it without success;I want to use$a=\frac{yz}{x^2},b=\frac{zt}{y^2},c=\frac{tx}{z^2},d=\frac{xy}{t^2},$and the Order inequality,but I'm not sure if it's right.Could anyone help me? Thanks a lot!

  • $\begingroup$ have you tried your substitution? $\endgroup$ – Dr. Sonnhard Graubner Dec 29 '16 at 17:54
  • $\begingroup$ Yes, but I'm not sure it's right $\endgroup$ – Zuo Dec 29 '16 at 17:57
  • $\begingroup$ your substitution works, but my proof uses Maple $\endgroup$ – Dr. Sonnhard Graubner Dec 29 '16 at 18:13


Let $f(x)=\frac{1-x}{x^2+x+1}+\frac{1}{3}\ln{x}$.

Hence, $f'(x)=\frac{(x-1)(x^3+6x^2+3x-1)}{3x(x^2+x+1)^2}$.

Which says that there is unique $0<x_1<1$, for which $f(x)\geq0$ for all $x\geq x_1$.

Easy to see that $x_1=0.0779...$,

which says that for $\min\{a,b,c,d\}\geq0.08$ our inequality is true.

Let $a<0.08$ and $g(x)=\frac{1-x}{1+x+x^2}$.

Hence, $g'(x)=\frac{x^2-2x-2}{(1+x+x^2)^2}$, which says that $\min\limits_{x>0}g=g(1+\sqrt3)$

and $g$ is a decreasing function on $(0,0.08]$.

Id est, $\sum\limits_{cyc}\frac{1-a}{1+a+a^2}\geq g(0.08)+3g(1+\sqrt3)=0.38...>0$


| cite | improve this answer | |
  • 2
    $\begingroup$ Nicely done! +1 $\endgroup$ – Macavity Dec 30 '16 at 2:02

If $abcd =1$, then put $f(x,y,z,w) = x+y+z+w$ subject to the constraint $g(x,y,z,w) = xyzw -1 =0$. Basically, we want to show that $a = b = c= d$ is a maximum when they all equal $1$.

So, we have, using lagrange multipliers,

  • $f_x = 1 = \lambda g_x = \lambda yzw$
  • $f_y = 1 = \lambda g_y = \lambda xzw$
  • $f_z = 1 = \lambda g_z = \lambda xyw$
  • $f_w = 1 = \lambda g_w = \lambda xyz$
  • $g(x,y,z,w) = xyzw -1 = 0$.

So, we have $xyz = \frac{1}{\lambda},$ hence $\frac{w}{\lambda} =1 \Rightarrow w = \lambda$.

But then $yz = \frac{1}{\lambda w} = \frac{1}{\lambda^2}$ so $x = \lambda$. Continuing in this fashion, we get $x = y =z = w =\lambda$, so $\lambda^4 = 1$. Clearly $\lambda =1$, rather than $\lambda = -1$, gives us our max for $f$.

Putting it all together, we have $\displaystyle \sum_{cyc} \frac{1-a}{a^2 +a +1} \ge 0$ for all $a,b,c,d$ such that $abcd =1$. This completes the proof.

| cite | improve this answer | |
  • $\begingroup$ How are $x, y, z, w$ related to $a, b, c, d$? And $f$ attains the minimum under the constraint $g=0$ when $x=y=z=w$, not the maximum (GM $\le$ AM). Am I misunderstanding something? $\endgroup$ – Martin R Dec 29 '16 at 19:16
  • $\begingroup$ You are right that it attains its minimum under the constraint $g=0$ when $x = y =z =w$, but when they equal $-1$. As we have shown, $f$ attains its max when $x=y=z=w =1$. $x,y,z,w$ are related to $a,b,c,d$ in that I prefer to use them as variables for functions. $\endgroup$ – David Bowman Dec 29 '16 at 19:37
  • $\begingroup$ Then it is unclear to me how the minimum of $\sum_{cyc} \frac{1-a}{a^2 +a +1} $ is related to the preceding arguments. $\endgroup$ – Martin R Dec 29 '16 at 19:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.